The Self-Defence Scroll of Kyokushinkai Karate: Analysing the Mokuroku Ōyama Masutatsu Received from Daitō-ryū Aikijūjutsu Master Yoshida Kōtarō - Gottner, Richárd Gábor (Távol-keleti Tanulmányok, 2025)
This paper aims to examine the self-defence techniques of the Kyokushinkai karate style, with a primary focus on one of its popular legends. According to the myth, the founder Ōyama Masutatsu had extensive training in the art of Daitō-ryū aikijūjutsu (the ancestor art of modern aikidō) under a master called Yoshida Kōtarō and received the ‘license of full transmission’ (menkyo kaiden) scroll of the Daitō-ryū school. The basis of this research is a high-resolution photocopy of the document (unfortunately due of copyright concerns, the picture of the scroll could not be featured in this paper; however a complete transcription and translation are included in the appendices). The paper dwells into the historical connections between the arts of Kyokuhsinkai, Daitō-ryū aikijūjutsu, and aikidō supported by circumstantial evidence and gives a brief technical comparation of the self-defence techniques of Kyokushinkai and the curricula of Daitō-ryū and aikidō. This is followed by a detailed analysis of the scroll itself, examining its structure and terminology and some techniques included in the scroll that are possibly featured in the Kyokushinkai curriculum, with special attention to stick and parasol techniques. The research gives a full analysis of Kyokushinkai self-defence techniques, which can be found in the original and revised editions of What is Karate?, This is Karate, Advanced Karate, and Mas Oyama’s Essential Karate, written by the founder of Ōyama Masutatsu himself, as well as Kyokushin Karate Self-Defense Techniques by high-ranking Kyokuhsinkai practitioner Bobby Lowe. The self-defence techniques found in the aforementioned texts show many similarities to the techniques published in various jūdō, aikidō, and aikijūjutsu books. Considering the historical facts (based on circumstantial evidence) that Ōyama Masutatsu trained in jūdō in the gym of Sone Kōzō, was a direct student of Daitō-ryū instructor Yoshida Kōtarō, and personally knew (allegedly even trained under) aikidō master Shioda Gōzō (founder of the Yōshinkan style of aikidō), it is highly likely that the parallels between the various self-defence techniques of Kyokushinkai karate, Kōdōkan jūdō, Yōshinkan aikidō, and Daitō-ryū aikijūjutsu are not merely coincidence. However, a thorough examination of the supposed Daitō-ryū scroll that Ōyama received from Yoshida Kōtarō revealed that the document itself is not a menkyo kaiden (license of full transmission) certificate. Furthermore, compared to the extant official scrolls of the Daitō-ryū tradition (Hiden mokuroku, Hiden okugi no koto), while the structure is similar, the scroll of Ōyama is certainly not a conventional transmission document of the Daitō-ryū school. The scroll that Yoshida granted to Ōyama is titled Yoshida-shiki sutekki-parasoru goshinjutsu mokuroku (Yoshida-style stick-parasol self-defence scroll), which (at the time of this research) appears to be a ‘one-of-akind’ transmission document on its own, officially signed by ‘The founder of Yoshida-style stickparasol self-defence, Daitō-ryū jūjutsu representative instructor, Yoshida Kōtarō’. The techniques listed in the scroll are unique in their terminology, and since there is no further information about the execution of these techniques, there is only a limited, assumption-based possibility to compare these techniques to those of the Daitō-ryū aikijūjutsu curriculum. For the same reason, it is also nearly impossible to certainly conclude whether the techniques from the scroll are featured as self-defence techniques in Ōyama’s karate books. Certain techniques found in the books could be matched with some technical names from the scroll; however, these connections cannot be stated with complete certainty. The research concluded in this paper answers the questions of whether Ōyama Masutatsu received a ‘license of full transmission’ in the Daitō-ryū school and whether there is in fact a possible connection between the Kyokushinkai self-defence techniques and the Daitō-ryū aikijūjutsu curriculum. While there are certainly Daitō-ryū techniques (among others) similar to those of the Kyokushinkai self-defence curriculum, and Ōyama without a doubt was a student of a Daitō-ryū representative instructor, he never received an official transmission license in the art of Daitō-ryū aikijūjutsu.